Dynamics simulations of photoinduced proton transfer reactions of 2-(2′-hydroxyphenyl)benzoxazole in the gas phase and its hydrated clusters - Rathawat Daengngern (2018)
The excited-state dynamics simulations of 2-(2′-hydroxyphenyl) benzoxazole (HBO) and hydrated HBO were performed on their lowest energy structures using RI-ADC(2)/SVP-SV(P). For free HBO, only syn-HBO can undergo tautomerization in the excited state. For HBO(H2O), two different pathways (A) the excited-state intramolecular proton transfer (PT) and (B) the excited-state intermolecular PT through hydrogen-bonded network occur. PT time of free HBO is ultrafast at 28 fs, whereas, the PT time of HBO(H2O) takes longer with time range of 43-193 fs depending on the initial structure. The slow PT process of HBO(H2O) is caused by competition between formations of intra- and intermolecular hydrogen bonds. © 2014 Elsevier B.V. All rights reserved.